Transparent conductive film

JP2026168975APending Publication Date: 2026-10-16OIKE & CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025062567
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-04
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、低抵抗であり、かつ、屈曲性が優れた透明導電性フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026168975000003
    Figure 2026168975000003
  • Figure 2026168975000001
    Figure 2026168975000001
  • Figure 2026168975000002
    Figure 2026168975000002
Patent Text Reader

Abstract

To provide a transparent conductive film that is low-resistance and has excellent flexibility. [Solution] A transparent conductive film comprising a first hard coat layer, a substrate, a second hard coat layer, an inorganic oxide layer, and a transparent conductive layer in this order, wherein the inorganic oxide layer contains silicon oxide, and the transparent conductive layer contains indium oxide and tin oxide and is crystalline, and the thickness of the transparent conductive layer is 50 to 160 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a transparent conductive film. More specifically, this invention relates to a transparent conductive film that is low-resistance and has excellent flexibility. [Background technology]

[0002] Conventionally, transparent conductive films have been used in various products such as touch panels, electronic paper, liquid crystal displays, dimmable sheets, and solar cells. Patent Document 1 proposes a light-transmitting conductive film comprising a transparent substrate and a light-transmitting conductive layer. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2020-136148 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] The light-transmitting conductive film described in Patent Document 1 includes a thickened light-transmitting conductive layer, such as ITO, to reduce resistance and improve conductivity. However, such a light-transmitting conductive film suffers from the drawbacks of poor flexibility and increased resistance.

[0005] This invention has been made in view of the above-mentioned conventional inventions, and aims to provide a transparent conductive film that has low resistance and excellent flexibility. [Means for solving the problem]

[0006] As a result of diligent research, the inventors focused on the composition, layer structure, and film thickness of the inorganic oxide layer and the transparent conductive layer, and found that by optimizing these, a transparent conductive film with low resistance and excellent flexibility could be obtained, thus completing the present invention. In other words, the transparent conductive film of the present invention that solves the above problems mainly includes the following components.

[0007] (1) A transparent conductive film comprising, in this order, a first hard coat layer, a substrate, a second hard coat layer, an inorganic oxide layer, and a transparent conductive layer, wherein the inorganic oxide layer contains silicon oxide, the transparent conductive layer contains indium oxide and tin oxide and is crystalline, and the thickness of the transparent conductive layer is 50 to 160 nm.

[0008] With this configuration, the transparent conductive film has low resistance and excellent flexibility.

[0009] (2) The resistivity of the transparent conductive layer is 2.0 × 10 -4 ~3.6×10 -4 A transparent conductive film as described in (1), having an impedance of Ω·cm.

[0010] With this configuration, the transparent conductive film has lower resistance and superior flexibility.

[0011] (3) The transparent conductive film described in (1) or (2), wherein the change in resistance value after 10,000 bending tests at a bending diameter of 10 mm is 1.15 or less.

[0012] With this configuration, the transparent conductive film has lower resistance and better flexibility.

[0013] (4) A transparent conductive film described in any of (1) to (3) that satisfies formula (1) below for all bending cycles when bending tests are performed at a bending diameter of 10 mm for 3,000, 5,000, 10,000, 15,000, 20,000, 30,000, 50,000, and 100,000 cycles. y ≤ exp(9.87 × 10)-6 x) (1) (wherein x is the number of bending cycles, and y is the change in resistance value after the bending test.)

[0014] According to such a configuration, the transparent conductive film has lower resistance and more excellent bendability.

[0015] (5) The transparent conductive film according to any one of (1) to (4), wherein the film thickness of the transparent conductive layer is 50 to 110 nm.

[0016] According to such a configuration, the transparent conductive film has more excellent bendability.

[0017] (6) The transparent conductive film according to (5), wherein the change in resistance value after 100,000 bending tests at a bending diameter of 10 mm is 1.20 or less.

[0018] According to such a configuration, the transparent conductive film has lower resistance and more excellent bendability.

[0019] (7) The transparent conductive film according to any one of (1) to (6), which has an undercoat layer between the second hard coat layer and the inorganic oxide layer.

[0020] According to such a configuration, the transparent conductive film has lower resistance and more excellent bendability. Effects of the Invention

[0021] According to the present invention, a transparent conductive film having low resistance and excellent bendability can be provided. Brief Description of the Drawings

[0022] [Figure 1] Figure 1 is a graph showing the relationship between the number of bending cycles and the change in resistance value in the bending test of the transparent conductive films of Examples and Comparative Examples. Modes for Carrying Out the Invention

[0023] <Transparent conductive film> A transparent conductive film according to one embodiment of the present invention comprises, in this order, a first hard coat layer, a substrate, a second hard coat layer, an inorganic oxide layer, and a transparent conductive layer. The inorganic oxide layer contains silicon oxide. The transparent conductive layer contains indium oxide and tin oxide and is crystalline. The thickness of the transparent conductive layer is 50 to 160 nm. The respective components are described below.

[0024] (base material) The substrate can be a resin film commonly used in transparent conductive films. For example, the substrate may be a plastic film or plastic sheet made of polyethylene terephthalate (PET), cycloolefin polymer (COP), polyimide (PI), polyamide (PA), polyethylene naphthalate (PEN), polycarbonate (PC), triacetylcellulose (TAC), etc. Alternatively, a flame-retardant substrate may be used, for example, by imparting flame retardancy to polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), etc. Among these, it is preferable that the substrate be made of a material with flexibility, such as a plastic film. This allows the transparent conductive film to be suitably used in a wide range of applications, such as electronic device components like displays and solar panels.

[0025] The thickness of the substrate is not particularly limited. For example, the substrate thickness is preferably 12 μm or more, more preferably 25 μm or more, and even more preferably 50 μm or more. Furthermore, the substrate thickness is preferably 200 μm or less, and more preferably 125 μm or less. By having the substrate thickness within the above range, the resulting transparent conductive film can exhibit appropriate rigidity, strength, and flexibility.

[0026] (Hard court layer (first hard court layer and second hard court layer)) The hard coat layer is a layer that increases the surface hardness of the transparent conductive film to prevent scratches, and is a protective layer with scratch resistance. The hard coat layer is provided on both sides of the substrate. That is, the transparent conductive film of this embodiment comprises a first hard coat layer, a substrate, and a second hard coat layer in this order. Hereafter, in descriptions of matters common to the first hard coat layer and the second hard coat layer, they will simply be referred to as the "hard coat layer". The resin material constituting each hard coat layer is not particularly limited. For example, the resin material constituting the hard coat layer may be a thermosetting resin (acrylic resin, phenolic resin, urea resin, melamine resin, unsaturated polyester resin, epoxy resin, silicon resin, polyurethane resin, diallyl phthalate resin), an ultraviolet curing resin (polyester acrylate, urethane acrylate, epoxy acrylate), a thermoplastic resin, an electron beam curing resin, or a two-component mixed resin. Among these, the resin material constituting the hard coat layer is preferably an ultraviolet-curable resin because it has a short curing time and exhibits excellent hard coating properties.

[0027] The method for forming the hard coat layer is not particularly limited. For example, the hard coat layer can be formed on the substrate by gravure coating, reverse coating, nanocoating, bar coating, die coating, dipping, screen printing, etc.

[0028] The thickness of the hard coat layer is not particularly limited. Preferably, the hard coat layer is 0.5 μm or more, and more preferably 1.0 μm or more. Furthermore, preferably, the hard coat layer is 10 μm or less, and more preferably 5 μm or less. By having a hard coat layer thickness within the above range, the transparent conductive film is given sufficient surface hardness and is resistant to scratches.

[0029] The hard coat layer may contain other additives. Specifically, the hard coat layer may contain a photopolymerization initiator, a curing agent, a curing accelerator, a crosslinking agent, a solvent, a reactive diluent, a photosensitizer, a surface conditioner, a slip agent, and the like.

[0030] The hard coat layer may contain a filler. By incorporating the filler into the hard coat layer, the transparent conductive film exhibits excellent transportability and winding property.

[0031] The constituent material of the filler is not particularly limited. For example, the constituent material of the filler may be inorganic particles (silicon oxide, zirconium oxide, titanium oxide, aluminum oxide, niobium oxide, calcium oxide), organic particles (polystyrene, polyurethane, acrylic resin, acrylic-styrene copolymer, benzoguanamine, melamine, polycarbonate) and the like. Among these, the filler is preferably silicon oxide.

[0032] The average particle diameter of the filler is not particularly limited. For example, the average particle diameter of the filler is preferably 1.0 μm or more, more preferably 1.5 μm or more. Further, the average particle diameter of the filler is preferably 7.0 μm or less, more preferably 5.0 μm or less.

[0033] (Inorganic oxide layer) The inorganic oxide layer is a layer containing silicon oxide, which is provided on the second hard coat layer.

[0034] The silicon oxide is a silicon oxide represented by the composition formula SiOₓ (0<x≦2, preferably 1≦x<2). The x value of SiOₓ may form a gradient film having a gradient in the thickness direction of the inorganic oxide layer, or may form a uniform film.

[0035] The silicon dioxide content in the inorganic oxide layer is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably 99% by mass or more. In this embodiment, the inorganic oxide layer may contain impurities that are unavoidably present. By having a silicon dioxide content within the above range, the transparent conductive film exhibits excellent light transmittance.

[0036] The thickness of the inorganic oxide layer is not particularly limited. For example, the thickness of the inorganic oxide layer is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more. Furthermore, the thickness of the inorganic oxide layer is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 10 nm or less. By having the thickness of the inorganic oxide layer within the above range, the resulting transparent conductive film exhibits excellent flexibility and adhesion.

[0037] The method for forming the inorganic oxide layer is not particularly limited. For example, the inorganic oxide layer can be formed by a dry coating method such as vacuum deposition, sputtering, or ion plating. Specifically, in the case of formation by sputtering, the inorganic oxide layer can be formed on a substrate by reactive sputtering using a silicon target in a mixed gas atmosphere of argon and oxygen.

[0038] (Undercoat layer) The transparent conductive film of this embodiment may have an undercoat layer between the second hard coat layer and the inorganic oxide layer. By providing an undercoat layer, the adhesion of the inorganic oxide layer can be improved, and the optical properties of the transparent conductive film can be improved.

[0039] The materials that make up the undercoat layer are not particularly limited. For example, the materials that make up the undercoat layer may include a main component, a curing agent, and additives made of polymer resin.

[0040] The materials that make up the main component are not limited. For example, the resin materials that make up the main component include thermosetting resins (acrylic resins, phenolic resins, urea resins, melamine resins, unsaturated polyester resins, epoxy resins, silicon resins, polyurethane resins, diallyl phthalate resins), UV-curable resins (polyester acrylate, urethane acrylate, epoxy acrylate), thermoplastic resins, electron beam-curable resins, two-component mixed resins, etc. Among these, the resin material that makes up the main component is preferably a UV-curable resin due to its short curing time.

[0041] The undercoat layer may contain inorganic particles. By including inorganic particles in the undercoat layer, the refractive index can be adjusted, thereby optimizing the optical properties of the transparent conductive film.

[0042] The material of the inorganic particles is not limited. For example, inorganic particles can be silicon dioxide, zirconium oxide, titanium dioxide, aluminum oxide, niobium oxide, zinc oxide, etc. Among these, zirconium oxide is preferred as the inorganic particle.

[0043] The average particle size of inorganic particles is not particularly limited. Preferably, the average particle size of inorganic particles is 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more. Preferably, the average particle size of inorganic particles is 100 nm or less, more preferably 70 nm or less, and even more preferably 50 nm or less.

[0044] The method for forming the undercoat layer is not particularly limited. For example, the undercoat layer can be formed by wet methods (coating methods) such as gravure coating, reverse coating, nanocoating, bar coating, die coating, dipping, and screen printing.

[0045] (Transparent conductive layer) The transparent conductive layer is formed on the side of the inorganic oxide layer opposite to the side facing the second hard coat layer. The transparent conductive layer contains indium oxide and tin oxide. That is, the transparent conductive layer contains indium tin oxide (ITO). The blending ratio of indium oxide (In2O3) and tin oxide (SnO2) in ITO is not particularly limited. For example, the blending ratio of tin oxide (SnO2) in ITO is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 7.0% by mass or more. Also, the blending ratio of tin oxide (SnO2) in ITO is preferably 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less. By having the blending ratio of tin oxide (SnO2) within the above range, the resulting transparent conductive film can exhibit low resistance and high conductivity.

[0046] Furthermore, the transparent conductive layer may contain other transparent conductive materials that exhibit transparency and conductivity, in addition to ITO, as long as they do not hinder the effects of the present invention. For example, other transparent conductive materials include metal oxides of metals such as indium, tin, zinc, gallium, antimony, titanium, silicon, zirconium, magnesium, aluminum, gold, silver, copper, palladium, and tungsten (excluding ITO). Among these, it is preferable that the other transparent conductive materials include aluminum oxide, indium zinc oxide (IZO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium cerium oxide (ICO), etc. The ITO content in the transparent conductive layer is preferably 95% by mass or more, more preferably 98% by mass or more, even more preferably 99% by mass or more, and may be 100% by mass. In this embodiment, the transparent conductive layer may contain impurities that are unavoidably present. As a result of providing such a transparent conductive layer, the transparent conductive film has excellent conductivity.

[0047] The transparent conductive layer of the present embodiment is crystalline. Therefore, the transparent conductive layer has a high carrier density, and can achieve lower resistance as compared with a case where it is amorphous. In addition, a transparent conductive film provided with such a transparent conductive layer has high stability against temperature and humidity, and deterioration over time is easily prevented. Furthermore, a transparent conductive film in which the transparent conductive layer is crystalline is excellent in light transmittance.

[0048] The specific resistance of the transparent conductive layer is preferably 2.0×10 -4 Ω·cm or more, more preferably 2.2×10 -4 Ω·cm or more, and even more preferably 2.4×10 -4 Ω·cm or more. The specific resistance of the transparent conductive layer is preferably 3.6×10 -4 Ω·cm or less, more preferably 3.4×10 -4 Ω·cm or less, and even more preferably 3.3×10 -4 Ω·cm or less. When the specific resistance of the transparent conductive layer is within the above range, the transparent conductive film has lower resistance and more excellent flexibility. In the present embodiment, the specific resistance can be calculated by multiplying the surface resistance value and the film thickness of the transparent conductive layer. The surface resistance value can be measured by a four-terminal four-probe method using a low resistivity meter (Loresta-GP MCP-T610, manufactured by Mitsubishi Chemical Analytech Co., Ltd.).

[0049] The film thickness of the transparent conductive layer is 50 to 160 nm. The film thickness of the transparent conductive layer may be 50 nm or more, preferably 55 nm or more, more preferably 60 nm or more, further preferably 70 nm or more, particularly preferably 80 nm or more, and even more particularly preferably 90 nm or more. In addition, the film thickness of the transparent conductive layer may be 160 nm or less, preferably 130 nm or less, and more preferably 110 nm or less. When the film thickness of the transparent conductive layer is less than 50 nm, the transparent conductive film has poor conductivity. On the other hand, when the film thickness of the transparent conductive layer exceeds 160 nm, the transparent conductive film has poor flexibility.

[0050] The surface resistance of the transparent conductive layer is preferably 60 Ω / □ or less, more preferably 55 Ω / □ or less, even more preferably 50 Ω / □ or less, and particularly preferably 45 Ω / □ or less. Because the surface resistance of the transparent conductive layer is within the above range, the transparent conductive film is suitable for applications requiring low resistance.

[0051] The method for forming the transparent conductive layer is not particularly limited. For example, the transparent conductive layer can be formed on an inorganic oxide layer using a composition constituting the transparent conductive layer by a dry coating method such as vacuum deposition, sputtering, or ion plating. Among these, the transparent conductive layer is preferably formed by reactive sputtering using a metal oxide target (ITO) by magnetron sputtering, because it is easy to form a thin film. In this case, for example, oxygen, water vapor, or other means such as ozone addition, plasma irradiation, or ion assistance may be used in combination.

[0052] As described above, according to this embodiment, the transparent conductive film has low resistance and excellent flexibility.

[0053] Regarding flexibility, the transparent conductive film of this embodiment exhibits excellent flexibility, resulting in a small change in resistance before and after the bending test when performing the following bending test.

[0054] (Conditions for the bending test) A bending test was performed using a small, benchtop durability testing machine (Yuasa System Equipment Co., Ltd., DLDM111LHA). A transparent conductive film was cut to a size of 2.5 cm x 10 cm, set in the machine with the transparent conductive layer facing upwards, and bent so that the transparent conductive layer was bent inwards. This counted as one bending cycle. The resistance value was measured before and after the test. The bending diameter was 10 mm, and the test speed was 60 reciprocations / minute. A multimeter (Kobayashi Measuring Instruments Co., Ltd., VOAC7411) was used to measure the resistance value. With the sample set in the durability testing machine, the resistance value was measured by touching the electrodes of the multimeter to a point 1 cm from each end of the sample in the longitudinal direction and 1.25 cm from the top end in the short direction, and measuring the resistance between the two terminals. The change in resistance value was confirmed by dividing the resistance value after the test by the resistance value before the test.

[0055] In this embodiment, the transparent conductive film preferably exhibits a resistance change of 1.15 or less after 10,000 bending tests at a bending diameter of 10 mm, more preferably 1.13 or less, and even more preferably 1.10 or less. This results in a transparent conductive film with lower resistance and superior flexibility.

[0056] In this embodiment, the transparent conductive film preferably exhibits a resistance change of 1.20 or less, and more preferably 1.15 or less, after 100,000 bending tests at a bending diameter of 10 mm. This results in a transparent conductive film with lower resistance and superior flexibility.

[0057] Furthermore, when the transparent conductive film of this embodiment is subjected to bending tests with a bending diameter of 10 mm at 3,000, 5,000, 10,000, 15,000, 20,000, 30,000, 50,000, and 100,000 bending cycles, it is preferable that the following formula (1) is satisfied at all bending cycles. As a result, the transparent conductive film has lower resistance and superior flexibility. y ≤ exp(9.87 × 10) -6 x) (1) (where x is the number of bends and y is the change in resistance after the bending test.)

[0058] Furthermore, regarding the presence and degree of curling, the transparent conductive film of this embodiment is less prone to curling. Therefore, when performing the following curl confirmation tests, curling is less likely to occur. Specifically, the maximum curl is preferably 30 mm or less, more preferably 20 mm or less, even more preferably 10 mm or less, and particularly preferably 5 mm or less. The minimum curl is preferably -30 mm or more, more preferably -20 mm or more, even more preferably -10 mm or more, and particularly preferably -5 mm or more. Having the curl within the above range provides excellent handling when using the transparent conductive film.

[0059] (Curl test) The curl evaluation is performed as follows: A 20cm square sample is heat-treated for crystallization, and the central part of the resulting transparent conductive film is cut out to a 10cm square. The cut-out sample is placed on a horizontal stand, and the height from the stand is measured at each of the four corners (1-4) of the sample. If the curl is directed towards the transparent conductive layer, the transparent conductive layer is placed on top, the height from the stand is measured, and the curl value is indicated by a minus sign (-). If the curl is directed towards the first hard coat layer, the transparent conductive layer is placed on the bottom, the height from the stand is measured, and the curl value is indicated by a plus sign (+). The maximum and minimum curl values ​​are confirmed at each of the four corners (1-4) of the sample. [Examples]

[0060] The present invention will be described more specifically below with reference to examples. The present invention is not limited in any way to these examples.

[0061] (Example 1) A 100 μm polyethylene terephthalate film (Lumirror, high-transparency grade with easy-adhesion layer on both sides, manufactured by Toray Industries, Inc.) was used as the substrate. A UV-curable polyfunctional acrylate resin was applied to one side of the substrate to a dry film thickness of 1.6 μm, and after drying, it was cured by UV irradiation to form a first hard coat layer (HC1). A UV-curable polyfunctional acrylate resin was applied to the other side of the substrate to a dry film thickness of 1.3 μm, and after drying, it was cured by UV irradiation to form a second hard coat layer (HC2). Subsequently, an inorganic oxide layer with a film thickness of 3 nm was formed on the second hard coat layer by sputtering, and a transparent conductive layer with a film thickness of 52 nm was formed on the inorganic oxide layer by sputtering. A Si target material was used to form the inorganic oxide layer, and the film deposition pressure with Ar gas and O2 gas introduced was 0.3 Pa. The Ar gas and O2 gas were introduced in a ratio of 9.3:1 (flow rate). For the formation of the transparent conductive layer, an indium oxide and tin oxide (ITO) target material (92.5% by mass of indium oxide and 7.5% by mass of tin oxide) was used. The magnetic field strength was set to 600G, and the deposition temperature (temperature of the roll in contact with the substrate during deposition) was set to -19°C. The deposition pressure with introduced Ar gas and O2 gas was set to 0.3 Pa, and the Ar gas and O2 gas were introduced in a flow rate ratio of 75:1. After the formation of the transparent conductive layer, it was heated in a 150°C constant temperature oven with forced air for 30 minutes to crystallize the formed transparent conductive layer and produce a transparent conductive film.

[0062] (Examples 2-4) A transparent conductive film was prepared in the same manner as in Example 1, except that the film thicknesses of the inorganic oxide layer and the transparent conductive layer were changed as shown in Table 1.

[0063] (Examples 5, 7, 9, 10) A transparent conductive film was prepared in the same manner as in Example 1, except that an undercoat layer (UD) was formed between the second hard coat layer and the inorganic oxide layer, and the film thicknesses of the inorganic oxide layer and the transparent conductive layer were changed as shown in Table 1. The undercoat layer was formed by the following method: An ultraviolet-curable resin composition, which was a mixture of an ultraviolet-curable polyfunctional acrylate resin and 15% by mass of zirconium oxide particles (average particle size 20 nm), was applied onto the second hard coat layer so that the film thickness after drying was 90 nm. After drying, it was cured by ultraviolet irradiation to form the undercoat layer.

[0064] (Examples 6 and 8) A transparent conductive film was prepared in the same manner as in Example 5, except that the film thicknesses of the inorganic oxide layer and the transparent conductive layer were changed as shown in Table 1, and far-infrared radiation was used for heating after the formation of the transparent conductive layer. The conditions for far-infrared heating after the formation of the transparent conductive layer were 160°C for 9 minutes.

[0065] (Comparative Example 1) As a substrate, a 100 μm polyethylene terephthalate film (Lumirror, a highly transparent grade with easy-adhesion layers on both sides, manufactured by Toray Industries, Inc.) was used. A first hard coat layer was formed on one side of the substrate. On the side of the substrate opposite to the side where the first hard coat layer was formed, an inorganic oxide layer with a thickness of 3 nm was formed by sputtering. A transparent conductive layer with a thickness of 52 nm was then formed on the inorganic oxide layer by sputtering. The methods for forming the first hard coat layer, the inorganic oxide layer, and the transparent conductive layer were carried out in the same manner as in Example 1 to produce a transparent conductive film.

[0066] (Comparative Examples 2-4) A transparent conductive film was prepared using the same method as in Comparative Example 1, except that the film thicknesses of the inorganic oxide layer and the transparent conductive layer were changed as shown in Table 1.

[0067] (Comparative Examples 5 and 6) A transparent conductive film was prepared in the same manner as in Example 1, except that an inorganic oxide layer was not formed and the thickness of the transparent conductive layer was changed as shown in Table 1.

[0068] (Comparative Example 7) A transparent conductive film was prepared in the same manner as in Example 1, except that the film thicknesses of the inorganic oxide layer and the transparent conductive layer were changed as shown in Table 1.

[0069] (Comparative Examples 8 and 9) A transparent conductive film was prepared in the same manner as in Example 5, except that an inorganic oxide layer was not formed and the thickness of the transparent conductive layer was changed as shown in Table 1.

[0070] (Comparative Example 10) A transparent conductive film was prepared in the same manner as in Example 5, except that the film thicknesses of the inorganic oxide layer and the transparent conductive layer were changed as shown in Table 1.

[0071] The transparent conductive films obtained in the above examples and comparative examples were subjected to the following tests: film thickness, surface resistance, resistivity, hydrochloric acid resistance test, curl, adhesion, adhesion after humid heat resistance test, and bending test. The results are shown in Tables 1 and 2.

[0072] <film thickness> The film thicknesses of the inorganic oxide layer and the transparent conductive layer were measured using a calibration curve quantitative analysis with an X-ray fluorescence analyzer (ZSX Primus IV, manufactured by Rigaku Corporation). <Surface resistance value> The surface resistance was measured using a low-resistivity resistivity meter (Loresta-GP MCP-T610, manufactured by Mitsubishi Chemical Analytec Co., Ltd.) with a four-terminal, four-probe method. <Specific resistance> Resistivity was calculated by multiplying the surface resistance by the film thickness. <Hydrochloric acid resistance test> A 5% by mass hydrochloric acid solution was prepared as the test solution. The surface resistance of the prepared transparent conductive film was measured before the hydrochloric acid immersion test, and then the film was immersed in the test solution for 5 minutes at 25°C. After immersion, the transparent conductive film was washed with water, dried, and then the surface resistance was measured again after the hydrochloric acid immersion test. The change in surface resistance was confirmed by dividing the post-test surface resistance by the pre-test surface resistance. If the change in surface resistance was 1.3 or less, it was determined that the transparent conductive layer had crystallized. The surface resistance was measured using a low-resistivity resistivity meter (Loresta-GP MCP-T610, manufactured by Mitsubishi Chemical Analytec Co., Ltd.) with a four-terminal, four-probe method. <Curl> A 20cm square sample was heat-treated for crystallization, and a 10cm square section was cut from the center of the resulting transparent conductive film. The cut sample was placed on a horizontal stand, and the height from the stand was measured at each of the four corners (1-4). If the curl direction was towards the transparent conductive layer, the transparent conductive layer was placed on top and the height from the stand was measured, and the curl value was expressed as a negative (-). If the curl direction was towards the first hard coat layer, the transparent conductive layer was placed on the bottom and the height from the stand was measured, and the curl value was expressed as a positive (+). The maximum and minimum curl values ​​were confirmed at each of the four corners (1-4) of the sample. <Adhesion> The adhesion of the transparent conductive film was evaluated using a grid peel test. Specifically, 11 cuts were made at equal intervals (1.5 mm) from the transparent conductive layer side, then rotated 90° and 11 more cuts were made at equal intervals (1.5 mm), creating 100 grid squares arranged in a 10x10 grid pattern. Cellophane tape (manufactured by Nichiban Co., Ltd., product number: CT405AP-18) was applied to this grid and adhered to the transparent conductive layer. Then, holding the end of the tape, the tape was instantly peeled off in a direction perpendicular to the bonded surface to check the degree of peeling of the layers. In the results, the numerator represents the number of squares that remained without peeling relative to the denominator (100 squares), and 100 / 100 represents a state of no peeling. <Adhesion after humidity and heat resistance test> The transparent conductive film was left to stand for 250 hours in a constant temperature and humidity chamber at 85°C and 85%RH, and then its adhesion was evaluated using the adhesion test method described above. <Bending Test> A bending test was performed on a transparent conductive film using a small, desktop durability testing machine (Yuasa System Equipment Co., Ltd., DLDM111LHA). Specifically, the fabricated transparent conductive film was cut to a size of 2.5 cm x 10 cm, set in the machine with the transparent conductive layer facing upwards, and bent so that the transparent conductive layer was bent inwards, which was considered one cycle. The number of bends was set to 3000, 5000, 10000, 15000, 20000, 30000, 50000, and 100000, and the resistance value was measured before and after each test. The bending diameter was 10 mm, and the test speed was 60 reciprocations / minute. A multimeter (Kobayashi Measuring Instruments Co., Ltd., VOAC7411) was used to measure the resistance value. The resistance was measured by placing the electrodes of a multimeter 1 cm from each end of the sample in the longitudinal direction and 1.25 cm from the top end in the short direction, while the sample was still set in the durability testing apparatus. The change in resistance was confirmed by dividing the resistance after the test by the resistance before the test.

[0073] [Table 1]

[0074] [Table 2]

[0075] As shown in Tables 1 to 2, the transparent conductive films of Examples 1 to 10 of the present invention exhibit low resistance and excellent flexibility.

[0076] Figure 1 is a graph showing the relationship between the number of bends and the change in resistance value in bending tests of transparent conductive films of the examples and comparative examples. In Figure 1, the dashed line in the graph is a curve represented by the following equation, and is an approximate curve based on the results of bending tests performed on Example 10 at 3000, 5000, 10000, 15000, 20000, 30000, 50000, and 100000 bends. y = exp(9.87 × 10) -6 x) (where x is the number of bends and y is the change in resistance after the bending test.)

[0077] As shown in Figure 1, the transparent conductive films of Examples 1 to 10 of the present invention showed little change in resistance even when the number of bends in the bending test was increased. In particular, the transparent conductive films of Examples 1 to 3 and Examples 5 to 9 showed even less change in resistance even when the number of bends in the bending test was increased. Therefore, it was found that the transparent conductive films of the present invention can be suitably used in various products such as touch panels, electronic paper, liquid crystal displays, dimming sheets, and solar cells.

Claims

1. The device comprises a first hard coat layer, a substrate, a second hard coat layer, an inorganic oxide layer, and a transparent conductive layer in this order. The inorganic oxide layer contains silicon dioxide, The transparent conductive layer contains indium oxide and tin oxide, and is crystalline. A transparent conductive film having a thickness of 50 to 160 nm for the transparent conductive layer.

2. The resistivity of the transparent conductive layer is 2.0 × 10 -4 ~3.6 x 10 -4 A transparent conductive film according to claim 1, wherein the density is Ω·cm.

3. The transparent conductive film according to claim 1 or 2, wherein the change in resistance value after 10,000 bending tests with a bending diameter of 10 mm is 1.15 or less.

4. A transparent conductive film according to claim 1 or 2, wherein when bending tests are performed with a bending diameter of 10 mm for 3,000, 5,000, 10,000, 15,000, 20,000, 30,000, 50,000, and 100,000 times, the following formula (1) is satisfied for all bending cycles. y≦exp(9.87×10 -6 x) (1) (where x is the number of bends and y is the change in resistance after the bending test.)

5. The transparent conductive film according to claim 1 or 2, wherein the thickness of the transparent conductive layer is 50 to 110 nm.

6. The transparent conductive film according to claim 5, wherein the change in resistance value after 100,000 bending tests with a bending diameter of 10 mm is 1.20 or less.

7. The transparent conductive film according to claim 1 or 2, further comprising an undercoat layer between the second hard coat layer and the inorganic oxide layer.

Citation Information

Patent Citations

  • Light transmissive conductive film

    JP2020136148A